2016
DOI: 10.1016/j.joca.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of intra- and peri-articular structural injuries in traumatic knee joint hemarthrosis – data from 1145 consecutive knees with subacute MRI

Abstract: ACL injury occurs in one out of two knees with traumatic hemarthrosis but only 12% are without concomitant structural injury. The overall rate of traumatic knee hemarthrosis and ACL injury is higher in men. In those aged 10-19 years, ACL rupture is more common among girls than boys whereas in those 16 years and younger, LPD is more common among boys than girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 35 publications
3
70
0
Order By: Relevance
“…30 Olsson et al reported that 88% of ACL injuries with traumatic hemarthrosis occur with concomitant structural injury with meniscus tears being the most common (55%). 31 In this study, an average of four other injured structures were seen with simultaneous ACL and PT ruptures. MRI should be used to evaluate patients presenting with traumatic hemarthrosis with suspicion for extensor mechanism, ligamentous, or meniscal injuries.…”
Section: Discussionmentioning
confidence: 70%
“…30 Olsson et al reported that 88% of ACL injuries with traumatic hemarthrosis occur with concomitant structural injury with meniscus tears being the most common (55%). 31 In this study, an average of four other injured structures were seen with simultaneous ACL and PT ruptures. MRI should be used to evaluate patients presenting with traumatic hemarthrosis with suspicion for extensor mechanism, ligamentous, or meniscal injuries.…”
Section: Discussionmentioning
confidence: 70%
“…Men had higher absolute PASE scores than women, and the differences between men and women were most pronounced in the subscale related to sports activities, indicating that the type of activity might also have an impact on cartilage thickness loss. Nevertheless, a higher physical activity level may be related to a higher frequency of trauma and injury , and thus to a greater loss of cartilage, but we adjusted for knee injury in our analyses. Muscle weakness may have also influenced the sex‐specific relationship between physical activity and cartilage thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this was not expected, the upregulated analytes in the serum related to either clotting or inflammation with the exception of the insulin‐like growth factor‐binding proteins. Pathways including complement and coagulation and platelet activation are to be expected due to hemarthrosis into the knee joint after injury . ACL injury creates an influx of pro‐inflammatory markers, protein mediators and blood into the joint, which may perpetuate cartilage damage .…”
Section: Discussionmentioning
confidence: 99%